2003
DOI: 10.1002/bem.10095
|View full text |Cite
|
Sign up to set email alerts
|

Elevated residential exposure to power frequency magnetic field associated with greater average age at diagnosis for patients with brain tumors

Abstract: To explore whether the age at cancer diagnosis was associated with residential exposure to magnetic field, we compared average ages at diagnosis for cases of leukemia, brain tumor, or female breast cancer with elevated exposure (magnetic flux density >or= 0.2 microT, or residential distance from major power lines 100 m from major power lines). Comparing with brain tumor cases with bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…Case-control studies that are based on death certificates revealed an association between adult brain tumor mortality and living less than 50 m (odd ratios, OR 1.10 95%, CI 0.74-1.64) [66] or 100 m (OR 2.99, 95%, CI 0.86-10.40) [67] from power lines. In a recent work, significant associations were found between the cumulated duration living at <50 m to high voltage lines (50/60 Hz, 0.3 µT) and all brain tumors (OR 2.94; 95%CI 1.28-6.75) and glioma (OR 4.96; 95%CI 1.56-15.77) [65], confirming previous studies [35,[66][67][68][69]. Contrasting results have been reported for brain tumors in children.…”
Section: Brain Tumorsupporting
confidence: 73%
“…Case-control studies that are based on death certificates revealed an association between adult brain tumor mortality and living less than 50 m (odd ratios, OR 1.10 95%, CI 0.74-1.64) [66] or 100 m (OR 2.99, 95%, CI 0.86-10.40) [67] from power lines. In a recent work, significant associations were found between the cumulated duration living at <50 m to high voltage lines (50/60 Hz, 0.3 µT) and all brain tumors (OR 2.94; 95%CI 1.28-6.75) and glioma (OR 4.96; 95%CI 1.56-15.77) [65], confirming previous studies [35,[66][67][68][69]. Contrasting results have been reported for brain tumors in children.…”
Section: Brain Tumorsupporting
confidence: 73%
“…This suggests that the effect could be due to shielding of the ambient weak extremely low frequency magnetic fields (ELF-MF) in the range of 10-240 Hz. As these ambient fields are primarily caused by electrical power distribution and use, and as they are generally less than 200 nT [Li et al, 2003], we decided to introduce ELF-MF of specific frequencies and amplitudes into the shielded environment. If these introduced ELF-MF abolished the induced analgesia, it would suggest that mice could sense such weak fields.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies of effects of magnetic fields on cell growth and proliferation have been carried out using mixture of in vitro models showed that acute exposure at 200mT decreased incorporation of [ 3 H] thymidine into the DNA of cancer cells (J. Wiskirchen, et al, 2000;C. Y. Li, et al, 2003).…”
Section: Introductionmentioning
confidence: 99%